Penatalaksanaan Fisioterapi Pada Fasciitis Plantaris Bilateral di RST Dr. Soedjono Magelang - Saputra, Bagus Ria Anjani Joko (2016)
Background: Fasciitis Plantaris is an inflammation of the fascia plantar caused by excessive elongation on fascia plantar which can result torn then arise an irritation in the fascia plantaris. Objective: To know benefit of modalities such as Ultrasounds (US) and Streching Exercise for reducing pain in Fasciitis Plantaris case. Result: After 4 times therapy, obtained reducing pain in the right heel are as follow: silent pain: T1: 2,1 to T4: 1,5 , tenderness T1: 4,2 to T4: 2,8 and pain motion T1: 2,4 to T4: 1,6. In left heel obtained reducing silent pain: T1: 2,1 to T4: 1,1 , tenderness T1: 4,2 to T4: 2,8 and pain motion T1: 2,4 to T4: 1,4. Conclusion: Ultrasounds and Streching Exercise can reduce pain in Fasciitis Plantaris condition.